2020
DOI: 10.1371/journal.pcbi.1007934
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities display alternative stable states in a fluctuating environment

Abstract: The effect of environmental fluctuations is a major question in ecology. While it is widely accepted that fluctuations and other types of disturbances can increase biodiversity, there are fewer examples of other types of outcomes in a fluctuating environment. Here we explore this question with laboratory microcosms, using cocultures of two bacterial species, P. putida and P. veronii. At low dilution rates we observe competitive exclusion of P. veronii, whereas at high dilution rates we observe competitive excl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…We have also found that the explanatory power of these four topological features increases when species attempt to invade multiple times (Figure 5C). While the number of alternative stable states has received most of the attention (Schröder et al, 2005;Serván & Allesina, 2020;Amor et al, 2020;Abreu et al, 2020), we show that the other three sources, especially in small communities, can contribute more to community predictability (Figure 5D). The trained neural network has predicted the observed predictability of two empirical assembly dynamics (Drake, 1991;Warren et al, 2003) well (Figure 6).…”
Section: Discussionmentioning
confidence: 82%
“…We have also found that the explanatory power of these four topological features increases when species attempt to invade multiple times (Figure 5C). While the number of alternative stable states has received most of the attention (Schröder et al, 2005;Serván & Allesina, 2020;Amor et al, 2020;Abreu et al, 2020), we show that the other three sources, especially in small communities, can contribute more to community predictability (Figure 5D). The trained neural network has predicted the observed predictability of two empirical assembly dynamics (Drake, 1991;Warren et al, 2003) well (Figure 6).…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, one can move beyond the single-species picture and consider instead the multi-species dissemination of mobile DNA (see [45] and references cited). Finally, these in silico experiments could be implemented in microbial microcosms [46, 47] as an intermediate step towards the application of terraformation strategies to real case studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ecological communities are constantly subject to perturbations arising from external factors, as well as from internal processes and interactions between community members. Environmental fluctuations through time have a fundamental influence on ecological communities: they may promote species coexistence, increase community diversity [45,46], contribute to the properties of stable states [37,47], and in some cases, facilitate abrupt regime shifts [47]. Our analysis of memory in perturbed communities is closely linked to recent studies analysing the response of experimental microbial communities to antibiotic pulse perturbation [48,49], or the impact of periodic perturbations on the evolution of antimicrobial August 17, 2021 11/28 resistance [34].…”
Section: Discussionmentioning
confidence: 99%